Pemodelan Spasial Untuk Penentuan Zonasi Rawan Kawasan Rawan Bencana Aliran Materil Erupsi Gunung Ungaran Menggunakan Aplikasi Sistem Informasi Geografis (SIG) - Rizki, Ananda Yusuf; Juhadi, Juhadi; Mochammad, Arifien (Geo-Image, 2018)
The purpose of this research is to model or describe the distribution of material flow eruption and to know the zoning vulnerable to the disaster of Mount Ungaran if one day there is a volcanic disaster. The method used to model the flow of eruption material is by using Monte Carlo methods of numerical simulation with the assumption that the topography determines the course of the flow. Determination of zoning of disaster prone areas is done by using overlay technique of eruption material flow aspect, land use condition aspect, morphology aspect, and sensitivity aspect to hazard represented by weight value. The result of this research is to produce the eruption material flow model at three different location points, the point is based on the chance of eruption activity. At the first point the area of eruption flow is 3.91ð‘˜ð‘š2, the second point is 1.25ð‘˜ð‘š2, and the third point is 2.51ð‘˜ð‘š2. Zoning of disaster prone areas produces disaster-prone class which is divided into very low, low, medium, and high class. At all three locations the eruption shows that the high disaster-prone zoning class has the smallest area compared to the extent of other disaster-prone zoning classes.